A new diatom (Bacillariophyta) found in a historic Hustedt sample from Java, description of Humidophila vandevijveri sp. nov. - Kochman-Kędziora, Natalia; Wetzel, Carlos E. (Phytotaxa, 2025)
During the examination of a historical sample collected by Friedrich Hustedt, an unidentified taxon belonging to the genus Humidophila was observed. This taxon could not be matched with any known species based on the currently available literature. Following a thorough morphological analysis and comparison, the taxon is described as Humidophila vandevijveri sp. nov. Its morphology is documented and illustrated using both light microscopy (LM) and scanning electron microscopy (SEM). Humidophila vandevijveri can be distinguished from closely related species by its stria density and distinctive ultrastructural features. A detailed morphological comparison with similar taxa is provided, along with information on the associated diatom assemblage.